Micro-physics simulations of columnar recombination along nuclear recoil tracks in high-pressure Xe gas for directional dark matter searches. (October 2015) - Nakajima, Y; Goldschmidt, A; Long, M; Nygren, D; Oliveira, C; Renner, J
Abstract: Directional sensitivity is one of the most important aspects of WIMP dark matter searches. Yet, making the direction of nuclear recoil visible with large target masses is a challenge. To achieve this, we are exploring a new method of detecting directions of short nuclear recoil tracks in high-pressure Xe gas, down to a few micron long, by utilizing columnar recombination. Columnar recombination changes the scintillation and ionization yields depending on the angle between a track and the electric field direction. In order to realize this, efficient cooling of electrons is essential. Trimethylamine(TMA) is one of the candidate additives to gaseous Xe in order to enhance the effect, not only by efficiently cooling the electrons, but also by increasing the amount of columnar recombination by Penning transfer. We performed a detailed simulation of ionization electrons transport created by nuclear recoils in a Xe + TMA gas mixture, and evaluated the size of the columnar recombination signal. The results show that the directionality signal can be obtained for a track longer than a few μm in some ideal cases. Although more studies with realistic assumptions are still needed in order to assess feasibility of this technique, this potentially opens a new possibility for dark matter searches.